Protein content of blood-derived extracellular vesicles: An approach to the pathophysiology of cerebral hemorrhage - Laso-García, Fernando; Piniella, Dolores; Gómez-de Frutos, Mari Carmen; Casado-Fernández, Laura; Pérez-Mato, María; Alonso-López, Elisa; Otero-Ortega, Laura; Bravo, Susana Belén; Chantada-Vázquez, María Del Pilar; Trilla-Fuertes, Lucía; Fresno-Vara, Juan Ángel; Fuentes, Blanca; et al. (Frontiers in Cellular Neuroscience, 2023)
Introduction: Extracellular vesicles (EVs) participate in cell-to-cell paracrine signaling and can be biomarkers of the pathophysiological processes underlying disease. In intracerebral hemorrhage, the study of the number and molecular content of circulating EVs may help elucidate the biological mechanisms involved in damage and repair, contributing valuable information to the identification of new therapeutic targets. Methods: The objective of this study was to describe the number and protein content of blood-derived EVs following an intracerebral hemorrhage (ICH). For this purpose, an experimental ICH was induced in the striatum of Sprague-Dawley rats and EVs were isolated and characterized from blood at baseline, 24 h and 28 days. The protein content in the EVs was analyzed by mass spectrometric data-dependent acquisition; protein quantification was obtained by sequential window acquisition of all theoretical mass spectra data and compared at pre-defined time points. Results: Although no differences were found in the number of EVs, the proteomic study revealed that proteins related to the response to cellular damage such as deubiquitination, regulation of MAP kinase activity (UCHL1) and signal transduction (NDGR3), were up-expressed at 24 h compared to baseline; and that at 28 days, the protein expression profile was characterized by a higher content of the proteins involved in healing and repair processes such as cytoskeleton organization and response to growth factors (COR1B) and the regulation of autophagy (PI42B). Discussion: The protein content of circulating EVs at different time points following an ICH may reflect evolutionary changes in the pathophysiology of the disease.